Inhibition of GSK3β rescues hippocampal development and learning in a mouse model of CDKL5 disorder - Fuchs, Claudia; Rimondini, Roberto; Viggiano, Rocchina; Trazzi, Stefania; De Franceschi, Marianna; Bartesaghi, Renata; Ciani, Elisabetta (Neurobiology of disease, 2015)
Mutations in the X-linked cyclin-dependent kinase-like 5 (CDKL5) gene have been identified in a rare neurodevelopmental disorder characterized by early-onset seizures, severe developmental delay, intellectual disability and Rett syndrome-like features. CDKL5 is highly expressed in the brain during early postnatal stages, suggesting its importance for brain maturation. Using a newly-generated Cdkl5 knockout (Cdkl5 −/Y) mouse, we recently found that loss of Cdkl5 impairs postnatal hippocampal development with a reduction in neuronal precursor survival and maturation. These defects were accompanied by increased activity of the glycogen synthase kinase 3β (GSK3β) a crucial inhibitory regulator of many neurodevelopmental processes. The goal of the current study was to establish whether inhibition of GSK3β corrects hippocampal developmental defects due to Cdkl5 loss. We found that treatment with the GSK3β inhibitor SB216763 restored neuronal precursor survival, dendritic maturation, connectivity and hippocampus-dependent learning and memory in the Cdkl5 −/Y mouse. Importantly, these effects were retained one month after treatment cessation. At present, there are no therapeutic strategies to improve the neurological defects of subjects with CDKL5 disorder. Current results point at GSK3β inhibitors as potential therapeutic tools for the improvement of abnormal brain development in CDKL5 disorder. •GSK3β inhibition restores hippocampal neuron survival in Cdkl5 KO mice.•GSK3β inhibition restores hippocampal synapse development in Cdkl5 KO mice.•GSK3β inhibition restores hippocampus-dependent behavior in Cdkl5 KO mice.•The effects of GSK3β inhibition outlast treatment cessation.•Results may have a translational impact for CDKL5 disorder.